The effect of pandemic on homebased tourism: post Covid-19 - Gloria Mayen Umukoro; Veronica Ebi Odey; Edisua Merab Yta (International Journal of Humanities and Innovation (IJHI), 2020)
The present study explores the effect of a pandemic on home-based tourism and tourists' decision to appreciate and patronize local indigenous sites, theater, and other tourism activities. An increase in the global spread of COVID-19 pandemic and incessant rise in deaths, especially in renowned destinations, travel restrictions and subsequent closure of international tourist sites; have pulled Nigerian tourists’ motivation away from international destinations. A survey of 250 frequent Nigerian travelers reported their cultural experiences before and during the pandemic and their decision to patronize Homebased tourist-oriented activities. The respondents' primary reasons for the push from international destinations were fear of COVID-19 infection, fear of death, and stigmatization. Significant reasons for pull were the low rate of spread, low deaths, and local traditional remedies availability. While the former was significant push factors identified, the latter were perceived as pull factors. However, respondents never considered facilities, weather, and airfares. Thus, this research significantly models local indigenous tourist sites' projection and cultural activities as tools for revitalizing home-based tourism in the post-COVID –19 era. It calls on government, tourism industry, and private firms to turn attention towards the revitalization of local indigenous tourist sites and cultural activities to attract tourists to enhance sustainable home-based tourism development.